Long-run consequences of informal elderly care and implications of public long-term care insurance - Thorben Korfhage (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
In this paper, I estimate a dynamic structural model of labor supply, retirement, and informal care supply, incorporating labor market frictions and the German tax and benefit system. I find that informal elderly care has adverse and persistent effects on labor market outcomes and therefore negatively affects lifetime earnings, future pension benefits, and individuals' well-being. These consequences of caregiving are heterogeneous and depend on age, previous earnings, and institutional regulations. Policy simulations suggest that, even though fiscally costly, public long-term care insurance can offset the personal costs of caregiving to a large extent - in particular for low-income individuals.
Keywords: I18; I38; J14; J22; J26; 330; long-term care; informal care; long-term care insurance; labor supply; retirement; pension benefits; structural model